Spatial distribution of Q fever in sheep and goats of selective villages of Punjab Province, Pakistan - Freeha Amin; Shahzad Ali; Ahmad Hassan; Imran Rashid; Heinrich Neubauer; Katja Mertens-Scholz (BMC Veterinary Research)
Abstract This study aimed to assess the geographical distribution of Q fever in sheep and goats in different areas of Punjab, Pakistan. Three hundred blood samples of small ruminants including sheep and goats were collected from 60 villages of three districts (Okara, Kasur, and Pakpattan) of Punjab Province Pakistan and tested for the detection of anti-Coxiella burnetii antibodies using a commercial Indirect ELISA kit. Data related to sampling location, host species, gender, age, and GPS coordinates were collected for spatial analysis. A surface plot was created using inverse distance weight (IDW) by interpolation of the Aeronautical Reconnaissance Coverage Geographic Information system (Arc GIS). The district Kasur (14%) and the tehsil Chunian (24%) had the most prominent Q fever prevalence in both species. No ovine males were seropositive but 19.2% of male goats were seropositive. No samples of sheep younger than 1 year were found seropositive. Gender in sheep and age in goats have to be considered as significant risk factors based on multiple logistic regression analysis. Based on spatial analysis, seropositivity for C. burnetii antibodies was more likely observed in villages of tehsil Kasur, Pattoki, Okara, Depalpur, and Renala Khurd in the case of goats while in case of sheep villages of tehsil Chunian, Renala Khurd and Pakpattan. The main outcome of this study is that Q fever-specific antibodies of C. burnetii are prevalent in the goat and sheep populations of the study area and we have identified potential risk zones. The findings of this study can be used for the control of Q fever in small ruminants of the study area to minimize the risk of this zoonosis in other animals and the associated human population.